'Won't get fooled again': How personal values shape leadership purpose, behavior and legacy. (17th May 2019) - Watton, Emma; Lichtenstein, Scott; Aitken, Paul
Abstract: While much has been documented about the construction of an individual's personal values, very little attention has been paid to how personal values connect with core aspects of leadership such as purpose, behavior and legacy. Through an expansion of Ken's recent work on this topic, the authors explore the impact of personal values-led leadership. A model of how personal values shape leadership purpose, behavior and legacy is introduced. These dimensions are then illuminated through interview data from senior managers from the financial services sector. The personal value impacts are examined in the context of the literature and implications for organizations and managers are drawn together.